Three‐dimensional electrical exploration methods for the mapping of polymetallic targets in Gansu Province, China. (4th June 2019) - Gong, Shengping; Yang, Yabin; Lin, Pinrong; Wu, Wenli; Zheng, Caijun; Shi, Fusheng; Wu, Xiaoping; Weng, Aihua; Zhang, Guangzhi; Gu, Guanwen; Ye, Yixin
ABSTRACT: We describe a three‐dimensional electrical exploration system, and its use in carrying out a three‐dimensional survey on a polymetallic deposit located in China's Gansu Province. A time‐domain‐induced polarization method, along with a controlled‐source audiomagnetotelluric method, was used to survey the same station points for comparison. Then, a three‐dimensional inversion based on the incomplete Gauss–Newton method (for time‐domain‐induced polarization) and a nonlinear conjugate gradient (for controlled‐source audiomagnetotelluric) method were developed and applied in order to model the data sets. Four subsurface targets were mapped by the three‐dimensional electrical exploration method. A strong correlation was found between the zones of the revealed ore‐bearing anomalies and the geological setting. Using the results of the three‐dimensional electrical exploration, we revealed the spatial distribution of the ore‐bearing stratum, as well as the relationship between the ore bodies and the stratum. The results potentially provided evidence for future interpretations of deep geological structures, along with evaluations of mineral resources.